2010
DOI: 10.3109/10641963.2010.503298
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Blood Pressure Response to Exercise – A New Portent of Masked Hypertension

Abstract: Masked hypertension (MHT) is a popular entity with increased risk of developing sustained hypertension, heart attack, stroke, and death. Subjects have normal blood pressure (BP) at office but elevated values at night so it is difficult to diagnose. Exaggerated blood pressure response to exercise (EBPR) is also a predictor of future hypertension. To investigate the relationship between these two entities, we evaluated 61 normotensive subjects with EBPR. The subjects underwent 24-h ambulatory blood pressure moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 39 publications
0
37
1
2
Order By: Relevance
“…In this subgroup, ExBPR is not useful to identify masked hypertension. However, it is still possible that in young patients with low BP levels, ExBPR is associated with masked hypertension, as has been previously described . In our population, we could not identify risk factors for masked hypertension.…”
Section: Discussionmentioning
confidence: 61%
“…In this subgroup, ExBPR is not useful to identify masked hypertension. However, it is still possible that in young patients with low BP levels, ExBPR is associated with masked hypertension, as has been previously described . In our population, we could not identify risk factors for masked hypertension.…”
Section: Discussionmentioning
confidence: 61%
“…43 Several studies have shown that the cardiovascular risk in patients with masked hypertension is elevated and that it is similar to the risk in patients with sustained hypertension. 44 Interestingly, a few studies 45,46 showed that an exaggerated blood pressure response during exercise was significantly correlated to the elevation of daytime and night time blood pressure as calculated by the ambulatory 24-h blood pressure measurement. On the basis of these studies, an exaggerated SBP response to exercise has been thought to reflect masked hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…It is a valuable means of identifying normotensive individuals at high risk for developing hypertension and further end-organ damage risk secondary to HT [38][39][40]. In addition, an association between exaggerated BP response to exercise and masked HT has been reported [7]. In a recent study, normotensive men with metabolic syndrome, but with exercise-induced HT, were found to have greater insulin resistance and lower HR variability indices [41].…”
Section: Discussionmentioning
confidence: 99%
“…Even in normotensive individuals, subjects with exaggerated BP responses to exercise were reported to be more prone to develop overt hypertension (HT) and associated unfavorable CV outcomes [6,7]. Impaired HR response to exercise, also known as chronotropic incompetence, is another parameter linked to adverse clinical outcomes in healthy adults and worse prognosis in patients with coronary artery disease (CAD) [8][9][10][11][12].…”
mentioning
confidence: 99%